Pulmonary Blastoma: A Rare Primary Lung Malignancy - Mahmoud S. Alahwal; Iqbal H. Maniyar; Faiza Saleem; Mariam Alshiekh (Case Reports in Medicine)
Pulmonary blastoma, a rare primary lung malignancy, is considered to be distinct from other lung tumors based on pathological features, clinical course, and prognosis. More than one hundred cases have been reported in literature highlighting an interesting fact about their distinctive biologic manner from histopathological features. Classic pulmonary blastoma is composed of a mixture of immature epithelial and mesenchymal tissue resembling fetal lung tissue. Surgery is the mainstay of treatment. The prognosis of this rare malignancy is poor and the overall 5-year survival is around 15%. Our patient presented with respiratory symptoms and was found to have right-sided chest wall mass. The patient underwent complete surgical excision followed by 6 cycles of platinum-based chemotherapy. The patient showed good subjective and objective response with no evidence of disease recurrence. We report this rare malignancy with a review of literature, and the potential to use adjuvant chemotherapy in the management of this condition.